Rift Valley fever - an emerging threat to livestock trade and food security in the Horn of Africa: A review. Poster presentation - Tibbo, Markos; Workalemahu, A.; Bonnet, P.; Domenech, J. (Institutions of Tropical Veterinary Medicine, 2001)
Rift Valley Fever (RVF) is a viral zoonotic insect-borne disease of livestock and human beings caused by a member of the Phlebovirus genus of the family Bunyaviridae. Being first recognised in the Rift Valley of Kenya at the turn of 20th century, several epidemics have occurred in eastern, southern, and northern Africa becoming a continental problem. The epidemics that occurred in Egypt in 1993 and current human and animal cases in Yemen and Saudi Arabia indicate that the potential exists for spread to other regions of the world outside the African continent. In recent years, livestock ban by Gulf countries for fear of the introduction of the disease has become a great problem of food security for livestock exporting countries in the Horn of Africa. Food insecurity in the Horn of Africa is a longstanding problem while the recent ban was imposed on eight countries before recovering from the recent drought. Between September and December 2000 a drop of livestock export by 92% was observed in Somalia. According to FSAU/FEWS (2001) excluding reduced governments revenue from livestock taxes, the estimated global loss of income at the Somali owner/producer (including livestock originated from Zone V of Ethiopia), lost producer income has reached 20-30 millions of USD, from October to December 2000. In Somalia, about 80% of foreign exchange earned from livestock exports are used to import basic food items. The decrease in imported commodities and falling of local currency against the US dollar and an increase in the prices of imported commodities were the first symptoms observed in Somalia and >Zone V of Ethiopia. This review emphasises on the risk of RVF on the future livestock economy and consequent food security in the Horn of Africa and analyses the current situation in severely suffering regions and suggests short- and long-term solutions for the problem.